Analisis Potensi Pengembangan Wisata Berkelanjutan: Studi pada Destinasi Wisata Ranca Upas, Ciwidey - Fadhiil, Muhamad Fuad; Muchatar, Fauzi Ramdhani (Pusat Studi Pariwisata Universitas Gadjah Mada, 2024)
Ranca Upas, known for its natural beauty and rich culture, offers significant opportunities for sustainable tourism development. This study involves collecting data through literature studies which include books, journals and articles related to Ranca Upas tourism in Ciwidey. The results of the analysis show that Ranca Upas has significant potential as a tourist destination with unique natural and interesting culture. Apart from that, this analysis also highlights the challenges faced by this tourist destination such as inadequate infrastructure and limited access. This article aims to provide in-depth insight into the potential of the Ranca Upas tourist destination and provide recommendations for sustainable tourism development that has a positive impact on the local community.